The Understanding of Political Elites on the Consensus of Nation and State Life - Sanusi, Sanusi; Yusuf, Rusli; Jannah, Miftahul (Jurnal Ilmiah Peuradeun, 2017)
This study discusses the understanding of the political elites in Kota Juang subdistrict, Bireuen District about the consensus of the nation and the state life. The state organizers both central and regional and all Indonesian citizens must be equally responsible for understanding and implementing the consensus values within their daily life. This research aims to (1) Describe the understanding of the political elites towards the consensus of the nation and the state life, (2) Describe the ability of the political elites to implement the consensus of the nation and the state life in the daily life. This research used a descriptive method with a qualitative approach. The findings of the research showed that: (1) Some political elites already understood the consensus of nation and state life in Kota Juang sub district, Bireuen District but some of them did not understand yet. (2) In general, the political elites in Kota Juang sub district, Bireuen District had implemented the consensus of the nation and state life in everyday life, but there were also political elites who did not know whether they had implemented it or not.